Ekstraksi dan Analisis Kimia Daun Gulinggang (Cassia alata Linn.) dengan Pelarut Air dan Etanol (The Extraction and Chemical Analysis of Gulinggang Leaves (Cassia alata Linn.) using Water and Ethanol as Solvents) - Karima, Rizka (Kementerian Perindustrian, 2017)
Gulinggang (Cassia alata Linn.) is a shrub that was used as a natural remedy by Japanese. However, the main compound of gulinggang in Kalimantan has not been identified. The purpose of the research were to identify its chemical and phytochemical compounds, as well as to determine the suitable methods and solvents for gulinggang extraction. The research used two methods of extraction: soxhlet apparatus and maceration; and three kinds of solution: water, ethanol 96% and water-ethanol (1:1). Gulinggang leaves extract was tested the chemical and phytochemical contents to identify the secondary metabolites compounds. The most dominant chemical compound found in the extracts is Methoxy, phenyl-oxime. The extraction method that gives maximum results on secondary metabolites of phytochemical compound was maceration methods using 96% ethanol. The result of secondary metabolites of phytochemical compound were alkaloids 0,04%; saponins 1,79%; tannins 0,10%; phenolics 5,12%; flavonoids as quercetin 0,09%; triterpenoid 0,05%; and steroids 1,02%.Keywords : Cassia alata Linn., extraction, gulinggang, phytochemical